Challenges among IIUM counseling practicum counselors: play therapy as a tool of collecting data - Rais, Haniza; Kassim, Siti Kholijah (2011)
Going through practical or internship experiences can be one of the most stressful moments in counseling training. Having gone through all the required courses is not a guarantee one is prepared to handle everything at the counseling site. Whatever is out there at the sites can be potential causes of stress. Supervision experience itself can be one of the stressors. Site visits by and communication with supervisors can easily raise their anxiety level. A study was conducted to explore challenges faced by IIUM practicum counsellors. With the use of play therapy activities using toys, crayons, objects, water color, clay, sandtray and play dough, etc. their struggles were explored and shared. This session will share the use of variety creative arts and play therapy with the practicum counselors in the process of assessing their coping reactions to the demand of tasks during these practical experiences. Data were collected through focus group discussion (FGD) in which drawings, play dough, clay, sand tray, etc. were included in the activities throughout the counselling supervision. The narratives from FGD and personal reflections or process journals were analyzed together with the products created. All forty practicum counsellors in the program of B Ed Guidance and Counseling who went through 12-week counselling practicum in the Klang Valley were involved in study. Practicum counselors expressed their challenges during internship and practicum through the use of creative arts. They found themselves to be more at ease and objective in sharing their issues based on their drawings and creations.